Serum neurofilament light levels in normal aging and their association with morphologic brain changes - Michael Khalil (Nature Portfolio, 2020)
Neurofilament (NfL) levels in CSF and blood have been established as a biomarker of neuronal damage in neurodegenerative diseases, and there is an age-dependent increase in NfL levels in CSF. Here the authors demonstrate that serum NfL levels increase in healthy aging people and predict and correlate with brain volume loss.